Analisis Nilai-Nilai Kepemimpinan Abdurrahman Wahid (Gus Dur) Dalam Pendidikan Moderasi Beragama - Zulfandika, Achfan Aziz; Wulandari, Sepya Catur (PGSD Universitas Muria Kudus, 2024)
This research aims to find out the values of religious moderation education in the leadership of Abdurrahman Wahid (Gus Dur).The research method uses library research or Library Research, by reviewing several library sources consisting of seven books and seventeen articles. The specified library source criteria include books or articles discussing Gus Dur, religious moderation, tolerance and education. Data collection techniques by reading literature obtained through Google Scholar, Connected Papers, Publish or Perish, Z-Library and library. The researcher carried out data analysis through several stages, namely content and discourse analysis, making reading conclusions, and explaining it logically and systematically.The research results that Gus Dur's religious moderation education values include several concepts, namely 1) Application of the concept of pluralism. 2) Uphold the values of tolerance. 3) His leadership applies the Wasathiyah concept which includes principles Tasamuh, Tawazun and Tawassuth. 4) There is no obligation or order in the government to form an Islamic system. 5) National orientation, based on nationalism and brotherhood, not the formalism of religious teachings. 6) Leadership that always avoids violence and upholds justice.